Counseling how to brush the teeth properly and correctly in elementary school: Penyuluhan cara menyikat gigi secara baik dan benar pada sekolah dasar - Eka Erwansyah; Devintha Virani; Fildayani Amir (Makassar Dental Journal, 2021)
Dental and oral health is one of the health problems that require continuous handling because it has a very broad impact, so it needs special treatment before it's too late. Accuracy in brushing teeth is the most important thing in taking care of the teeth. Counseling is performed to produce individuals who understand and are able to practice good and correct methods of brushing teeth, so they will become healthy habits and behaviors to maintain teeth and mouth healthies. This type of activity uses coun-seling methods with flipcharts and dental models. During the counseling, participants were quite active in responding, answer-ing questions, and conducting toothbrush simulations. The technique of counseling brushing teeth is effectively to increase the knowledge of participants where seen from the direct practice of how to brush teeth.